Feeding littles & beyond : 100 baby-led-weaning-friendly recipes the whole family will love - Maffucci, Ali; McNamee, Megan; Delaware, Judy (Avery, an imprint of Penguin Random House, 2022)
"An inspirational, accessible family cookbook that offers everything a parent needs to bring joy and love back into the kitchen, by the baby and toddler feeding experts behind Feeding Littles and the New York Times bestselling cookbook author of Inspiralized"--